Respuesta :
Answer:
y+1=3(x+1)
Step-by-step explanation:
The slope of the given line is ...
m = (y2 -y1)/(x2 -x1)
m = (3 -(-3))/(2 -0) = 6/2 = 3
The point-slope form of the equation of a line with slope m through point (h, k) is ...
y -k = m(x -h)
Whe have m=3, h=-1, k=-1, so the equation is ...
y +1 = 3(x +1)
The equation, in the point-slope form of the line the parallel to the given line and passes through the point (-1,-1) is y + 1 = 3(x+ 1)
The equation of an aline in point-slope form
The equation of an aline in point-slope form is expressed as:
y - y 1 = m(x-x1)
m is the slope
(x1, y1) is any point on the line
Given the following
(x1, y1) = (-1, -1)
m = 3+3/2+0
m = 6/2
m = 3
Substitute into the formula
y - (-1) = 3(x-(-1))
y + 1 = 3(x+ 1)
Hence the equation, in the point-slope form of the line the parallel to the given line and passes through the point (-1,-1) is y + 1 = 3(x+ 1)
Learn more on equation of a line here: https://brainly.com/question/18831322